Dimensionamiento y construcción de una bicicleta eléctrica - Herrera Ordóñez, Jean Paúl (2022)
In this degree work, topics such as the dimensioning of an electrical system, selection of mechanical components, selection of a bicycle frame, through which an electric bicycle was assembled, were addressed. Information extracted from web pages, scientific articles, mechanics books, degree works referring to conventional and electric bicycles was compiled, with which it was possible to establish a state of the art capable of offering the reader a broad perspective on bicycle engineering. The theoretical foundations provided in the state of the art were developed, such as the selection process of the appropriate material for the bicycle frame, the modeling and simulation of the frame in SolidWorks ® software, the dimensioning and selection of the electric motor, as well as the electronic components. In addition, the selection of the mechanical components of the bicycle was carried out and subsequently the assembly process was carried out. The performance testing phase allowed knowing the behavior of the prototype on different routes and it was possible to determine the autonomy of the battery. Finally, it was concluded with the economic technical analysis of the prototype in which comparisons were made between three means of transport to determine energy consumption, pollutant emissions and costs. Keywords: Selection of materials, electric motors, electric batteries, structural design, performance tests, energy consumption, emissions, costs